Everything counts! : 52 remarkable ways to inspire excellence and drive results - Blair, Gary R. (Gary Ryan) (Wiley, 2010)
Everything Counts! is an execution strategy for inspiring excellence and driving exceptional results. Too many people and organizations are mired in a mediocrity of their own making. They focus their attention and efforts on getting the big things right, but they ignore the little things that often make a big difference. As a result, reputations are damaged, brands diluted, and loyalty is lost by blatant disregard for the small stuff which negatively impacts the customer experience. For years, we've been taught not to sweat the small stuff, but in the real world of business, Everything Counts. E.